INFLUENCE OF FAMILY STYLE AND PEER PRESSURE ON ADOLESCENTS’ SUBSTANCE EXPLOITATION IN KARU METROPOLIS - Omaku, Sani A. S.; Ogah, Nafisat S.; Godiya, Audu (African Journal of Social and Behavioural Sciences, 2023)
The study examined the influence of family style and peer pressure on adolescent substance exploitation in Karu metropolis using the survey design method. A total of 230 adolescents between the ages of 14-20 years old took part in the study. Participants consisted of 180 males and 50 females whose selection was based on snowball sampling technique. Results showed no significant difference between family style and adolescent’s substance exploitation [F (1, 229) = 0.06, P<. 05], implying that adolescent substance exploitation was not based on family style where adolescents came from. However, findings confirmed a negative relationship between peer group pressure and substance exploitation among adolescents as [r = .93; P<.05] and a negative relationship between family relations and substance exploitation among adolescents [r = -0.35, P<.01]. The study identified that, socially, adolescent substance exploitation is alarmingly increasingly and therefore, recommends that educational institutions and parent/teachers’ associations should remind parents and caregivers of their moral and social responsibility to their children’s upbringing as so doing will promote desirable standards and ensure a healthy Nigerian society.